Work travel, knowledge industries, and the environment - Lassen, Claus (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
This article is a part of an ongoing PhD-project at Aalborg University which draws the attention towards so-called ‘knowledge industries’ as transport-generating enterprises. The national and international statistics show that air-traffic and international work-related trips has increased enormously during the past decades. Because of the more aggressive impact of CO2 emissions in the higher strata of the atmosphere, their threat to the global climate from aeroplanes is more serious than what is the case for similar travelling distances at surface level. In this article I hypothesize that there is a connection between aeromobility, knowledge industries and environmental impacts. The object for this article is therefore to examine the driving forces, mechanisms and patterns of meaning beyond the increased international long-distance work-mobility. Such mobility practise is what I term highly aeromobilised. To do so, the article draws theoretically on ‘sociology of mobility’ and empirically on a case study that involves two Danish cases from the ‘knowledge enterprises’. The main point in the article is that it is necessary to understand the social basis for long-distance work travel and to rethink central concepts of travel, tourism and working life to understand and describe this kind of international mobility in the knowledge industries. The boundary between work and tourism, work and play, pain and pleasure is not distinct and there is a very complex connection between travel, work, tourism and play in the knowledge industries. The article therefore ends up by arguing that policy and planning have to understand this complex social relation when tools to ensure ‘sustainable mobility’ are discussed in the future.